Pengaruh Model Pembelajaran Discovery Learning Pada Pembelajaran Tematik Di MI Ma'arif Pulutan - Rini Verary Shanthi; Nurul Maghfiroh (Universitas Wahid Hasyim Semarang, 2020)
Abstract Discovery Learning is a learning model which makes students get involved in the problem solving for developing knowledge and skill. The using of discovery learning model can involve the students in problem solving activities, independent learning, thinking critically, comprehending and learning creatively. This learning model is along with thematic learning approach. The thematic learning is designed based on certain integrated themes to connect and correlate some subjects in order to give meaningful experiment for students. This research objects is to know the influence of discovery learning model to the thematic learning in MI Ma’arif Pulutan. The quaitative research methods was used in this reasearch. The primary data was collected from the teachers and the students’ report of study. The secondary data was obtained from the principal and the vice of principal of curriculum. The data collection was processed by triangulation technique and the data analysis was processed by qualitative method. Based on the result of the research can be concluded that the discovery learning model on thematic learning approach can simplify the teacher to teach the students, the students can comprehend the material easily, and can increase the learning outcomes level of the students in MI Ma’arif Pulutan